INFLUENCE OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT OF TOURISM ON THE FORMATION OF MARKETING STRATEGIES OF TOURIST COMPANIES - KRUPENNA, Inga; HORBATIUK, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the impact of the modern trend of strengthening the concept of sustainable development of tourism on the formation of marketing strategies of tourism companies, on updating tourism marketing tools that are becoming more personalized, inclusive, "smart", digitized, partnership and ecological. It is noted that the marketing strategies of sustainable tourism are formed in the direction of achieving changes that ensure the transition to a higher level of balance of the economic, social and environmental development of the tourism industry. The changes accompanying the post-Covid sustainability trends of the tourism industry are considered. It was emphasized that despite the importance of travelers’ health and safety, price transparency, value, environment and environment of service provision, gastronomy, emotions, accessibility, inclusiveness and barrier-freeness have gained importance. positive consumer experience and sustainable business practices. It is noted that when choosing a place of rest and travel, tourists rarely refer to ratings and assessments of competitiveness, they go where they feel comfortable, where they can get the impression of rest. Important indicators of the tourist reputation of a country are the ratings of the world’s authoritative Internet aggregates working in the field of tourism. It is noted that the decisive factor in the choice of a travel destination and the formation of tourist flows is the attractiveness and hospitality of local residents, therefore formal and informal ratings of countries and territories with the friendliest residents are updated. Attention is focused on the popularity of the new concept of travel - "slow tourism", on the formation of new models and trends in the tourism sector in the long and short term: increasing the role of national and regional tourism; increased attention to sustainable development and responsible tourism; technology and digitalization of the tourism sector; "smart tourist destinations", cognitive tourism; new generations of consumers. It was concluded that the marketing strategies of tourism companies will be influenced by: growing economic and geopolitical challenges; consequences of the Covid-19 pandemic; war in Ukraine; the rapid increase in energy prices and the increase in the price of tourist packages; the growing role of inclusivity, the concept of accessible tourism, sustainability in the recovery of the sector, the sustainability of supply chains and the ecosystem of the tourism and travel industry; investments in digital solutions and technologies; the influence of social networks on the choice of place, time and format of travel.